Implementasi Metode Pembelajaran Beyond Center and Circle Times (BCCT) di RA Al-Huda Kota Samarinda Dengan Metode Rolling Sentra: Meningkatkan Kualitas Pembelajaran - Julaiha, Siti; Malik, Lina Revilla (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2024)
This study aims to describe the implementation of the Beyond Center and Circle Time (BCCT) learning method with the student rotation method from one class to another (Rolling) at RA Al-Huda Samarinda City, and its impact on improving the quality of early childhood education. The research method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The research results show that the teachers at RA Al-Huda have implemented rolling by dividing the class into several activity centers. Each center is rotated in turn, so that students have an equal opportunity. This rolling system has proven effective in increasing children's interest in learning, creating a variety of engaging activities for children, and developing children's abilities holistically. However, there are challenges in managing transitions between centers, but the teachers at RA Al-Huda overcome these challenges by providing individual guidance, using motivational techniques, and simplifying transitions between centers. Overall, the implementation of the BCCT method with a rolling system at RA Al-Huda has had a positive impact on improving the quality of early childhood education.